Demokratie? Eine Debatte. Mit Beiträgen von G. Agamben, A. Badiou, D. Bensaïd, W. Brown, J.-L. Nancy, J. Rancière, K. Ross und S. Žižek. Suhrkamp Verlag 2012 - Fries, Martin (HannahArendt.net, 2013)
Besprechung.